Large-scale filamentary structures around the virgo cluster revisited - Kim, Suk H.; Lisker, Thorsten (Arxiv, 2016)
We revisit the filamentary structures of galaxies around the Virgo cluster, exploiting a larger dataset based on the HyperLeda database than previous studies. In particular, this includes a large number of low-luminosity galaxies, resulting in better sampled individual structures. We confirm seven known structures in the distance range 4~